2004
DOI: 10.1111/j.1478-4408.2004.tb00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a new cationic bleach activator on a hydrogen peroxide bleaching system

Abstract: The performance of a cationic bleach activator, N- [4-(triethylammoniomethyl)benzoyl]caprolactam chloride, was evaluated in a hot peroxide bleaching process. The effect of time, temperature and the concentrations of hydrogen peroxide and activator on the bleaching of cotton fabric was investigated using a central composite experimental design. Temperature was found to be the most significant parameter. By adding the cationic activator it was possible to achieve a level of whiteness comparable to a typical comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 1 publication
1
29
0
1
Order By: Relevance
“…This can be explained with the cationic character of PBA, which enabled higher consumption and a greater bleaching effect than the anionic PAA (Lavri č et al 2007;Lim et al 2004). Figure 5 shows the kinetics of HP and pernonanoic acid (PNA) generation and consumption in the presence of NOBS.…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained with the cationic character of PBA, which enabled higher consumption and a greater bleaching effect than the anionic PAA (Lavri č et al 2007;Lim et al 2004). Figure 5 shows the kinetics of HP and pernonanoic acid (PNA) generation and consumption in the presence of NOBS.…”
Section: Resultsmentioning
confidence: 99%
“…A clear explanation must address a series of chemical reactions related to TBBC. In most of the research related to bleach activators attempted for industrial textile bleaching, it has been stated that the activated peroxide bleaching system could provide an enhanced whiteness by using bleach activators and a large excess of hydrogen peroxide at a molar ratio of around 1:10 and at relatively high pH of around 11.5, assuming that bleach activators and alkaline hydrogen peroxide could simultaneously work on bleaching (Matthews 1999;Scarborough and Matthews 2000;Cai et al 2001;Wang and Washington 2002;Gursoy et al 2004a, b;Lim et al 2004;Lim et al 2005;Cai and Evans 2007). This is plausible because hydrogen peroxide dissociates at pH 11 to 11.5 to release perhydroxyl anions that directly bleach fibers (Zeronian and Inglesby 1995).…”
Section: Chemistry Of Tbbcmentioning
confidence: 99%
“…Using bleaching activators, a relatively benign bleaching system can be conducted at lower temperature and reduced time relative to conventional peroxide bleaching, thereby leading to reduced fiber damage. Cationic bleach activators (CBAs) are a class of quaternary ammonium peracid precursors (Willey et al 1997), as exemplified by N-[4-(triethylammoniomethyl) benzoyl]caprolactam chloride (TBCC) (1) (Gursoy et al 2004a, b;Lim et al 2004;Lim et al 2005). However, TBCC is sensitive to hydrolysis in aqueous solutions .…”
Section: Introductionmentioning
confidence: 99%
“…Cationic bleach activators have been designed to exhibit substantivity for the negatively charged surface of cellulosic fibers in aqueous solution to provide enhanced bleaching efficiency when compared with anionic bleach activators, especially at low temperatures. Previous studies have shown that cationic bleach activators can be applied in cold padbatch and hot peroxide bleaching processes for cotton (Gürsoy et al 2004a, b;Lim et al 2004Lim et al , 2005Križman et al 2007). In particular, N-[4-(triethylammoniomethyl)benzoyl]caprolactam chloride (TBCC), shown in Fig.…”
Section: Introductionmentioning
confidence: 99%